The Erosion of Healthcare and Scientific Integrity: A Growing Concern - Brücher BL (Journal of Healthcare Leadership)
Björn LDM Brücher1– 4 1European Academy of Sciences and Arts (EASA), Salzburg, Austria; 2Theodor-Billroth-Academy® with its INCORE, International Consortium of Research Excellence, Munich, Germany; 3Theodor-Billroth-Academy® with its INCORE, International Consortium of Research Excellence, Sacramento, CA, USA; 4Department of Surgery, Medical University Lausitz – Carl-Thiem, Cottbus, GermanyCorrespondence: Björn LDM Brücher, Email b.bruecher@mul-ct.deBackground: Tremendous achievements in healthcare and science over the past 200 years have enhanced life expectancy in parallel with a shift from dogma to humanistic liberal education. Advancements in cancer have included vaccines treating causes of cancer (eg, hepatitis C- induced liver cancer and human papillomavirus-induced cervical cancer) along with improved cancer survival in children. In contrast, developments in cancer, frequently touted as “discoveries” or “breakthroughs” in media headlines, have been demonstrated to be ephemeral rather than game changers. In reality, cancer incidences are increasing, and relapse and mortality rates have not changed substantially. By this, we are experiencing today similar challenges to those before the so-called Humboldt reform. The trend towards managerialism with a focus on quantity in health care and science endangers their integrity.Methods: Due to the complexity of integrity of healthcare and science, in-depth contemplation of this review contains foundations of actions in healthcare and science, information regarding cancer, as an example, quantity focus of healthcare, technology, publishing, marketing and media, predatory publishers, followed by psychologic and sociologic aspects which influence our perception.Results: A complex paradoxical transformation has occurred, in which quality and humanism have been replaced by quantity, revenue, and marketing, together with “citation silence”, (ignoring original findings), and increased corruption and misconduct. This shift explains why the integrity of healthcare and science is being eroded.Conclusion: Countries and societies are only as strong as their healthcare and science, both of which are only as strong as their emphasis on quality and integrity. Awareness of this situation may represent a first step toward a renewed focus on accountability. Keywords: healthcare, science, integrity, quality, quantity, accountability